The impact of international volunteers on education quality in developing countries ‒ An assessment of organisations’ volunteer recruitment and management practices - Hechenberger, E. (Revista Iberoamericana de Estudios de Desarrollo)
International volunteering and service (IVS) organisations expanded dramatically in size, reach and variety in the past decades. While volunteering is socially valued, we know little about the real impact it has on host communities. I take a segregated approach to assess the potential impact of IVS on education, the most popular activity. Using Sherraden et al.’s (2008) conceptual model of IVS impacts, I explore the effects that individual and institutional factors have on education outcomes. In addition to the literature review on IVS and education quality, qualitative data on 12 sending organisations’ volunteer recruitment and management practices was gathered. Findings suggest that teaching qualifications and expertise are among the most significant factors but are often not prioritized in the recruitment criteria. Yet, existing limitations can be compensated through effective programming. Some patterns can be identified when comparing the common practices of the four types of organisations reviewed.